Risiko Paparan Debu/Particulate Matter (PM2,5) Terhadap Kesehatan Masyarakat (Studi Kasus: Tempat Pembuatan Batu Bata di Desa Kaloran, Kecamatan Ngronggot, Nganjuk) - Dzahabiyyah Dwi Putri Ridayanti; Khambali Khambali; Hadi Suryono (FORIKES, 2022)
Firewood and corn cobs as the main fuel in the brick burning process can produce particulate matter (PM2.5) pollutants which can pose a risk to the health of the surrounding community. The purpose of this study was to analyze the risk of exposure to dust/PM2.5 on the health of the community around the brick-making site of Kaloran Village, Ngronggot District, Nganjuk Regency. This type of research is descriptive using a cross-sectional design with Environmental Health Risk Analysis (ARKL) studies. The sampling technique was purposive sampling based on certain characteristics, with a sample size of 306 households. Air sampling was carried out at 4 locations where the bricks were burned. Data collection techniques were carried out by means of interviews, measurements, and observations. The data analysis method was a risk analysis to determine the characterization of risk in the community which is said to be